Autonomous ships in maritime education model course 7.01 - Belev, Blagovest (Array, 2021)
The fourth industrial revolution is already a fact. It is manifested in the emerging automation of many processes in shipping, which until recently have been highly dependent on the competence of the people who manage them. The analysis of navigational accidents invariably touches the human factor and involves it in the reasons for their occurrence. The statistics are discouraging and the lack of competence of seafarers is always present in the reports of the investigating authorities. The idea of creating and implementing autonomous ships is cited as a lifeline to overcome the shortcomings that disturb the industry due to the human factor. A few authors in their publications point out many unresolved issues, one of which is related to the education and competence of service personnel. The existing International Convention for Standards of Training, Certification and Watchkeeping of Seafarers does not cover unmanned ships. The mandatory and recommended competencies in it are addressed to the people on board. Some maritime educational institutions have introduced the concept of “autonomous ship” in their curricula, such as Nikola Vaptsarov Naval Academy, Varna and Faculty of Maritime Study, Split. There are probably others who think ahead, but this approach is not enough because unmanned ships are already a fact in the maritime industry. This article aims at exploring the possibilities for supplementing the curricula of maritime training institutions with appropriate subjects for the new realities in shipping.